Fluorescent C ii* 1335Å emission spectroscopically resolved in a galaxy at z = 5.754. (29th May 2019) - Bosman, Sarah E I; Laporte, Nicolas; Ellis, Richard S; Ouchi, Masami; Harikane, Yuichi
ABSTRACT: We report the discovery of the first spectroscopically resolved C ii /C ii * 1334, 1335 doublet in the Lyman-break galaxy J0215–0555 at z Lyα = 5.754. The separation of the resonant and fluorescent emission channels was possible thanks to the large redshift of the source and long integration time, as well as the small velocity width of the feature, 0.6 ± 0.2Å. We model this emission and find that at least two components are required to reproduce the combination of morphologies of C ii * emission, C ii absorption and emission, and Lyman-α emission from the object. We suggest that the close alignment between the fluorescence and Lyman-α emission could indicate an ionization escape channel within the object. While the faintness of such a C ii /C ii * doublet makes it prohibitively difficult to pursue for similar systems with current facilities, we suggest it can become a valuable porosity diagnostic in the era of JWST and the upcoming generations of ELTs.